Joint optimization of operational cost and carbon emission in multiple data center micro-grids - Hao, Xiaobo; Liu, Pengcheng; Deng, Yanhui; Ye, Guisen (Frontiers in Energy Research, 2024)
To improve the paper quality and address the concerns raised by the reviewers, we have carefully revised our paper. The revisions are also red highlighted with a yellow background for better readability.research on data center carbon emission reduction ignored the influence of efficiency of power supply system. Thirdly, the carbon tax is taken into consideration in our paper, which can help to simplify the bi-objective optimization problem of cost and carbon emission into a single objective optimization problem.Q2: The literature review is not comprehensive enough. There are existing relevant works on the data center operational optimization that are not discussed. The paper should clearly position itself against current research.